Do weight categories prevent athletes from relative age effect? - Delorme, N. (Journal of Sports Sciences, 2014)
The aim of this study was to investigate whether weight categories prevent young athletes from being exposed to a relative age effect. The dates of birth of all French female (n = 727) and male (n = 5440) amateur boxers who participated in the 2010-2011 season were collected from the federation database. The dates of birth of all French male professional boxers (n = 354) were also collected. The results show an absence of a relative age effect among French female and male amateur boxers. The results also show an absence of this phenomenon among French male professional boxers. The male 18-18+ age category reveal an inverse relative age effect. This inverse relative age effect might be interpreted as the result of a strategic adaptation from relatively younger children who shift from one sport to another where there are weight categories in order to ensure fair competition. The results of this study suggest that the weight category system is a possible solution within the relative age effect phenomenon.